Calcium-dependent desensitization of vanilloid receptor TRPV1: a mechanism possibly involved in analgesia induced by topical application of capsaicin - Vyklický, Ladislav; Nováková-Toušová, Karolina; Benedikt, Jan; Samad, A; Touška, Filip; Vlachová, Viktorie (Physiological research, 2008)
The rationale for the topical application of capsaicin and other vanilloids in the treatment of pain is that such compounds selectively excite and subsequently desensitize nociceptive neurons. This desensitization is triggered by the activation of vanilloid receptors (TRPV1), which leads to an elevation in intracellular free Ca2+ levels. Depending on the vanilloid concentration and duration of exposure, the Ca2+ influx via TRPV1 desensitizes the channels themselves, which may represent not only a feedback mechanism protecting the cell from toxic Ca2+ overload, but also likely contributes to the analgesic effects of capsaicin. This review summarizes the current state of knowledge concerning the mechanisms that underlie the acute capsaicin-induced Ca2+-dependent desensitization of TRPV1 channels and explores to what extent they may contribute to capsaicin-induced analgesia. In view of the polymodal nature of TRPV1, we illustrate how the channels behave in their desensitized state when activated by other stimuli such as noxious heat or depolarizing voltages. We also show that the desensitized channel can be strongly reactivated by capsaicin at concentrations higher than those previously used to desensitize it. We provide a possible explanation for a high incidence of adverse effects of topical capsaicin and point to a need for more accurate clinical criteria for employing it as a reliable remedy.
Keywords: Animals; Calmodulin; analgezie; Capsaicin; kalmodulin; membránové potenciály; kationtové kanály TRPV; Analgesics; lidé; TRPV Cation Channels; baryum; vápník; Ion Channel Gating; Models, Molecular; bolest; gating iontového kanálu; molekulární modely; Administration, Topical; Calcium; aplikace lokální; kapsaicin; analgetika; krysa rodu Rattus; Pain; zvířata; Barium; Rats; Analgesia; Membrane Potentials; Humans